A survey of post-transplant direct non-medical and indirect costs for recipients and caregivers at five transplant centers in Thailand - Sangmala, Pannapa; Bunworasate, Udomsak; Niparuck, Pimjai; Kitiyakara, Chagriya; Pongskul, Cholatip; Townamchai, Natavudh; Jaroenpatarapesaj, Sirima (The Journal of Chulabhorn Royal Academy, 2020)
Background: A previous study in Thailand examined the cost-effectiveness model of an oral form of anti-cytomegalovirus drug, valganciclovir, versus intravenous ganciclovir in post-transplant care for national policy decision. Due to valganciclovir gave lower costs for hospital visits, but higher drug costs than ganciclovir. This study therefore presented the direct non-medical and indirect costs from the same study, to enable a fuller description how these cost parameters simulated in the model came from. Methods: A total of 87 kidney and 67 bone marrow transplant recipients in Thailand were followed-up 1 year after transplantation at three kidney and two bone marrow transplant centers. They were surveyed to identify the direct non-medical costs arising from their transplant. These included out-of-pocket payments for traveling to centers, food during visits, and hotel stays. Patient and caregiver productivity losses were included as indirect costs using the human capital approach and estimated from Thai Gross National Income per capita. Mean and standard error (SE) were used to estimate all costs. Results: The mean daily traveling costs were 400.4286 Thai baht (THB) (SE = 28.1833). The incidental daily costs for food were 162.7792 THB (SE = 13.6701). The annual accommodation cost was 402.2727 THB (SE = 200.2631), and the individual daily productivity loss was estimated as 390.7139 THB for patients and 189.0142 THB for caregivers. Conclusions: This study identified the unit costs for patients visiting hospitals during 1 year of post-transplant care. These costs can be used to supplement information about the management patterns for valganciclovir or ganciclovir modelling, and may also be useful in economic evaluation of other post-transplant care for future decision-making in Thailand.